Implementasi Pembiayaan Kredit Usaha Rakyat (KUR) Mikro Syariah Pada Bank Syariah Indonesia KCP Rungkut 1 - Athiya Shinta Wulandari; Arin Setiyowati (Universitas Muhammadiyah Ponorogo, 2022)
People's Business Credit (KUR) is one of the government's efforts to develop the productive sector, in particular by helping business people to obtain financing, through the People's Business Credit (KUR) program. The current government program that is underway in the context of developing micro, small and medium enterprises is known as the People's Business Credit. This research uses qualitative research methods with the Library Research approach. The data source used in this study is a secondary data source. The data collection technique used in this research is data triangulation. With data analysis starting from the data collection process, then compiling, categorizing data, looking for themes so that it can be interpreted. So that from this study the results obtained from the implementation of People's Business Credit (KUR) financing at BSI KCP Surabaya Rungkut 1, that the advantages of KUR financing are that it can increase the capacity of micro business competitiveness.